CDMF-RELSUS concept: reliable products are sustainable products – influences on product design, manufacturing and use phase. (1st January 2013) - Bracke, Stefan; Michalski, Jens; Inoue, Masato; Yamada, Tetsuo
Based on the customer's product recognition, sustainability and environmental protection become key sales arguments within the automotive industry. The customer expects reduced resource consumptions, environmental friendly manufacturing and a long usage phase. Especially product reliability saves resources in many ways. Manufacturer product reliability is associated with higher development and production costs, but, especially in industries with high innovation rates, customer usage is limited to the product actuality, which leads to two key questions: a) How much product reliability makes sense out of the view of manufacturers, customers and environmental protection? b) What is the impact of reliable products regarding the reduction of resources? This paper outlines the 'Collaborative development, manufacturing and field verification for higher product reliability towards sustainability (CDMF-RELSUS) concept' focusing on influences and interdependences of product development, manufacturing planning and field observation regarding the successor development including the combination of reliable and sustainable product characteristics.